Sinking in sports ; Wanted barrio doctors ; Racing across American [Videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
President Ramos clean-up on Philippine Sports Commission through Eric Buhain's confession at his frustrating experiences with the government's sports agency. Health Secretary Juan Flavier offers a nice salary for those willing to serve in areas that have been doctorless for ten years. A debate o the kind of medical education that we give and the kind of doctors we get. The bicycle racer Maui Reynante being invited to join the World's longest bicycle race.
Sinking in sports (16 min.) -- Wanted: barrio doctors (20 min.) -- Racing across America (15 min.)
VHS
Keywords: Reynante, Manuel -- Interviews; Philippine Sports Commission -- Corrupt practices; Cyclists -- Philippines; Physican services utilization -- Philippines; Physicians -- Philippines; Sports -- Corrupt practices. -- Philippines